Retrospective Study on Ganglionic and Nerve Block Series as Therapeutic Option for Chronic Pain Patients with Refractory Neuropathic Pain - J. D. Gerken; T. Fritzsche; C. Denke; M. Schäfer; S. Tafelski (Pain Research and Management)
Objective. Current recommendations controversially discuss local infiltration techniques as specific treatment for refractory pain syndromes. Evidence of effectiveness remains inconclusive and local infiltration series are discussed as a therapeutic option in patients not responding to standard therapy. The aim of this study was to investigate the effectiveness of infiltration series with techniques such as sphenopalatine ganglion (SPG) block and ganglionic local opioid analgesia (GLOA) for the treatment of neuropathic pain in the head and neck area in a selected patient group. Methods. In a retrospective clinical study, 4960 cases presenting to our university hospital outpatient pain clinic between 2009 and 2016 were screened. Altogether, 83 patients with neuropathic pain syndromes receiving local infiltration series were included. Numeric rating scale (NRS) scores before, during, and after infiltration series, comorbidity, and psychological assessment were evaluated. Results. Maximum NRS before infiltration series was median 9 (IQR 8–10). During infiltration series, maximum NRS was reduced by mean 3.2 points (SD 3.3, p<0.001) equaling a pain reduction of 41.0% (SD 40.4%). With infiltration series, mean pain reduction of at least 30% or 50% NRS was achieved in 54.2% or 44.6% of cases, respectively. In six percent of patients, increased pain intensity was noted. Initial improvement after the first infiltration was strongly associated with overall improvement throughout the series. Conclusion. This study suggests a beneficial effect of local infiltration series as a treatment option for refractory neuropathic pain syndromes in the context of a multimodal approach. This effect is both significant and clinically relevant and therefore highlights the need for further randomized controlled trials.